A importância de Scotus na concepção de história de Arendt - Bortolotti, Ricardo Gião [UNESP] (Universidade Estadual de Maringa, 2013)
The objective of this study is to discuss the notion of history in Arendt, from the importance that needs the thought of Duns Scotus, particularly with regard to the primacy of the will. For the author, Scotus was a medieval thinkers to emphasize the role of free will as power in the face of intellect attached to the natural activity. The freedom to get an act featuring a world ruled by contingency. Now, for Arendt, that freedom is consistent with your idea of authentic political, and base a public space, defined by word and action of individuals. The history, which takes place from political activity, received various treatments, from Greek antiquity to the modern conception of process. It joined the idealistic conceptions, establishing universal ways of defining the future. However, if freedom is to characterize the vita activa, the history must seek the meaning of the facts to scrutinize their singular aspects, which fell to the continuo of universal explanation of the official history. It is, therefore, to approach the history from the perspective of singular narrative, from the spectators, those who founded the public space. Hence the importance of bipolar concepts such as nature and freedom, necessity and contingency, will and intellect, as Scotus.

O objetivo deste trabalho é abordar a noção de história em Arendt, a partir da importância que dispensa ao pensamento de Duns Scotus, particularmente no que concerne à primazia da vontade. Para a autora, Scotus foi um dos pensadores medievais a ressaltar o papel da vontade como potência livre, frente à potência intelectual, presa à atividade natural. A liberdade de começar um ato caracteriza um mundo regido pela contingência. Ora, para Arendt, essa liberdade condiz com a sua ideia de política autêntica e que funda o espaço público, definido pela palavra e pela ação dos indivíduos. A história, que tem lugar a partir da atividade política, recebeu diversos tratamentos, desde a Antiguidade grega à concepção moderna de processo. Uniu-se a concepções idealistas, estabelecendo modos universais de definir o futuro. No entanto, se a liberdade deve caracterizar a vita activa, a história deve buscar os significados dos fatos ao perscrutar seus aspectos singulares, que se reduziram ao contínuo da explicação universal da história oficial. Trata-se, pois, de abordar a história da perspectiva da narrativa singular, a partir dos espectadores, daqueles que fundam o espaço público. Daí, a importância das noções bipolares, como natureza e liberdade, necessidade e contingência, vontade e intelecto, conforme Scotus.
The presence of Scotus in the sense of history of Hannah Arendt
Keywords: Action; contingency; Freedom; Nature; Political; Will; Ação; Contingência; Liberdade; Natureza; Política; Vontade